Analysis of labour by modified WHO partograph in primigravida and multigravida term patients: an observational study - Yadava, Pushpa A.; Gogia, Nausheen N.; Mehta, Shital T.; Jani, Shashwat K.; Mittal, Silkey (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The World Health Organization (WHO) recommends the use of a partograph to follow labor and delivery, with the aim of improving health care and reducing maternal and foetal mortality. The partograph is a graphic representation of events of labour and is an effective visual resource for early detection of abnormal progress of labour and prevention of prolonged labour. The aim of this study is to use partograph to monitor labor, analyse cervical effacement and dilatation, uterine contraction, foetal presentation while avoiding uterine hypo-stimulation, hyperstimulation and reducing the risk of sepsis, obstructed labor or postpartum haemorrhage (PPH). Methods: This was a single year hospital-based observational study conducted in 2021 of the deliveries in Sardar Vallabhbhai Patel Institute of Medical Sciences and Research (SVPIMSR) and Sheth V.S General Hospital, Ahmedabad. Analysis of labor of 60 randomly selected patients was done using WHO modified partograph. The patients were classified as primigravida and multigravida. The partograph recording started at 4cm dilatation, continuous maternal and foetal monitoring was ensured throughout the labor and partogram was plotted against time in hours. Any deviations from the normal course were recorded. Results: In this observational study, 60 patients were analysed. They were classified into primigravida and multigravida and based on the recordings from partograph further classified into mode of delivery. 3 out of 26 primigravida and 1 out of 34 multigravida patients underwent caesarean deliveries. 25 patients crossed the alert line and 4 patients crossed the action line. 5 deliveries out of 60 had APGAR score of <7 at 5 minutes. Conclusions: The WHO modified partograph is highly effective in reducing both maternal and neonatal morbidity. It is an excellent visual resource to analyse cervical effacement and dilatation, uterine contraction and foetal presentation in relation to time. It is effective in early detection of abnormal progress of labor, prevention of prolonged labor, obstructed labor, PPH and improvement in neonatal outcome.